Strategy Development for the Agribusiness Microfinance Institution (LKMA) in Kendal Regency - Edy Purwanto; Ari Dwi Astono; Wahyu Imam Santoso (Jurnal AGRISEP, 2025)
Agribusiness Microfinance Institutions (LKMA) are micro-scale financial institutions prioritized for farmers initiated by the Ministry of Agriculture of the Republic of Indonesia. The number of LKMA in Kendal Regency in 2015 was 277 in 20 sub-districts. In 2022, there were 28 active LKMA and 249 inactive LKMA. Many inactive LKMA are due to poor LKMA governance, so farmers cannot access financing for their business capital. This study uses a qualitative case study approach. The population in this study consisted of all LKMA leaders in Kendal Regency, and the sampling technique used was purposive sampling. The number of samples was the Head of LKMA Blorok, LKMA Anugerah Tani Makmur, LKMA Mekar Arum, LKMA Sendangmulyo, LKMA Sido Makmur, LKMA Sukma Sejahtera, LKMA Bina Tani, LKMA Tanam Sari, LKMA Gondang and LKMA Karangsari Sejahtera. Data analysis includes data reduction, data presentation, and conclusions using data validity techniques, namely data triangulation. The results of the study stated that the condition of LKMA in Quadrant I is growth with strategies that must be implemented, namely increasing capital through cooperation with the private sector and the government, the need for regional government regulations on LKMA governance, increasing soft skills and managerial skills in LKMA management, and providing agricultural insurance for LKMA members. This study implies that the Kendal Regency Government can make Regional Regulations on LKMA management guidelines to be used as guidelines in implementing LKMA governance for the sustainability of LKMA and improving the economy of farmers in Kendal Regency.